RETRACTED: Guidance and Training in Digital Financial Bookkeeping for UMKM (MSME) Batik Kantil Malang: THIS ARTICLE HAS BEEN RETRACTED - Ita Rifiani Permatasari; Lilies Nur Aini; Umi Khabibah; Fullchis Nurtjahjani; Jatrifia Ongga Sinatriya; Yulis Nurul Aini (Transpublika Publisher, 2025)
RETRACTION NOTICE RETRACTED: Guidance and Training in Digital Financial Bookkeeping for UMKM (MSME) Batik Kantil Malang Ita Rifiani Permatasari*, Lilies Nur Aini, Umi Khabibah, Fullchis Nurtjahjani, Jatrifia Ongga Sinatriya, Yulis Nurul Aini. (2025). Guidance and Training in Digital Financial Bookkeeping for UMKM (MSME) Batik Kantil Malang. JOURNAL OF SUSTAINABLE COMMUNITY SERVICE , 5(2), 57-63. https://doi.org/10.55047/jscs.v5i2.928 The editors of JOURNAL OF SUSTAINABLE COMMUNITY SERVICE are retracting the above article. Following notification from the corresponding author, it has been determined that this article had previously been published in Jurnal Pengabdian Kepada Masyarakat (Polinema), Vol. 11 No. 2 (2024), available at https://jurnal.polinema.ac.id/index.php/jpkm/article/view/5239. At the time of submission, the author(s) indicated to the editors that the work was unpublished. The prior publication was not disclosed to the editors, and no permission to republish was obtained. This constitutes a case of redundant (duplicate) publication. The retraction is requested by the author(s) and approved by the editors. The editors were not aware of the prior publication at the time of peer review and acceptance. This retraction notice supersedes the article in all versions. This retraction is issued in accordance with the journal's Publication Ethics policy (https://transpublika.co.id/ojs/index.php/JSCS/PUBLICATION-ETHICS) and the COPE Retraction Guidelines (https://publicationethics.org/guidance/guideline/retraction-guidelines). The Editors, JOURNAL OF SUSTAINABLE COMMUNITY SERVICE Date: 21 May 2026